932. COELOGYNE ANNAMENSIS. (16th May 2020) - Schuiteman, André; Cribb, Phillip; Want, Terry; King, Christabel
Summary: Coelogyne annamensis Rolfe is illustrated, and compared with C. assamica Linden & Rchb.f.), C. brunnea Lindl. and other members of Coelogyne section Fuscescentes Pfitzer & Kraenzl. Suggestions for its successful cultivation are given.